Europe's 2020 - innovation and creative capability of the Baltic Sea Region - Jan Wedemeier; Mirko Kruse (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2018)
The ongoing structural change towards the service and knowledge societies, innovations, and the increasing integration of markets will have considerable influence on the European Union, particularly on the Eastern members of EU. In March 2010, the European Commission released the Europe-2020 strategy, which shall push the EU to be the smartest and most competitive region in the world. Among the European Union members, the Baltic Sea countries are effective in bringing up innovative cluster solutions, cooperation between science and business. Innovations are crucial for further economic development and prosperity. However, the innovation headline indicators are ambitiously defined targets of the Europe-2020 strategy. The paper at hand analyses and highlights the innovation and creative capability within the Europe 2020 strategy framework.
Keywords: O3; R11; R12; Z1; 330; innovation; Baltic Sea Region; Europe 2020; creative sector